Association of the dietary inflammation index DII with the prevalence of chronic kidney disease in patients with hypertension - Xin Lu; Shuang Zhou; Shujun Liu; Yundong Shi (Renal Failure)
Background and objective Chronic kidney disease (CKD) is a global health concern that is frequently associated with hypertension. Inflammation is an important factor in the development of both illnesses. The Dietary Inflammation Index (DII) has evolved as a way to measure how much a diet can cause inflammation, which may impact CKD, especially in hypertensive persons. The study’s goal is to investigate the link between DII and the occurrence of CKD in hypertensive individuals.Methods This study examined data from 22940 hypertensive patients from 1999 to 2018 of the National Health and Nutrition Examination Survey (NHANES). The DII was computed using 28 dietary components. CKD was diagnosed based on the estimated glomerular filtration rate and urine albumin-to-creatinine ratio. The link between DII and CKD was explored using sampling-weighted logistic regression and restricted cubic splines.Results Higher DII scores were shown to be strongly related with an increased risk of CKD. In the fully adjusted model, this connection remained consistent across demographic and clinical categories.Conclusions The study found a strong association between a pro-inflammatory diet and an elevated risk of CKD in hypertensive individuals, emphasizing the potential of dietary changes in CKD management.